The Implementation of Prenatal Exercise to Reduce Back Pain in Third Trimester Pregnant Women - Fisca Jevanesia, Nawa; Roslianti, Elis (Yayasan Inspirasi El Burhani, 2025)
Background: Pregnancy is a physiological process that induces various bodily changes in women, including hormonal, postural, and biomechanical adaptations. Back pain is a common complaint among pregnant women, particularly during the third trimester. Prenatal exercise serves as a non-pharmacological intervention designed to enhance physical fitness, strengthen muscles, and alleviate pregnancy-related discomfort. Objective: This case study examines the implementation of prenatal exercise to reduce back pain in Mrs. Y, a third-trimester pregnant woman in Banjarsari District, Ciamis Regency. Method: Using a qualitative descriptive methodology with a maternity nursing care process approach (assessment, nursing diagnosis, planning, implementation, and evaluation), data were collected through interviews, physical examinations, observations, and documentation review. Result: Initial assessment revealed Mrs. Y experienced intermittent back pain described as